Adverse effects of GLP – 1 Receptor Agonists - Anna Kasprzak; Monika Kułaga; Monika Grzybek; Diana Mazur-Lesińska; Barbara Szostak; Sylwia Wielgosz-Biała; Krzysztof Tyszkiewicz; Borys Łozowski; Małgorzata Kasprzak; Barbara Wilczyńska (Journal of Education, Health and Sport)
Introduction and purpose Glucagon-like peptide-1 receptor agonists (GLP – 1 RAs) are indicated in type 2 diabetes (T2D) and obesity because of their high efficacy in controlling blood glucose levels and inducing weight loss. Patients may develop gastrointestinal adverse effects (GI AEs) such as nausea, vomiting, diarrhoea, constipation and, less commonly, pancreatitis and cholelithiasis. In addition, a recent retrospective cohort study suggested a possible association between nonarteritic anterior ischaemic optic neuropathy (NAION) and the use of one of the GLP – 1 RAs, semaglutide. The aim of this article is to review the side effects associated with GLP – 1 RAs therapy.